(untitled) (Revista de Ciências Agroveterinárias, 2024)
The main objective of the Climate and Physiographic Suitability Mapping System (AptClim) is to allow the user to assess the climate and physiographic suitability of an area of interest using different criteria and climatic periods. AptClim was developed on the Google Earth Engine (GEE) platform and is available at https://ee-vianna.projects.earthengine.app/view/aptclim. Using AptClim, it is possible to map and evaluate the climatic and physiographic suitability considering the monthly climatology of minimum and maximum temperatures and rainfall, as well as the slope of the relief. In this article we present AptClim, how to access it, the method used to calculate suitability and a case study to analyze the variation in climate suitability for the juçara palm (Euterpe edulis) over the last four decades. In the case evaluated, AptClim proved to be an accessible, practical and agile tool for analyzing climate suitability, generating suitability maps, calculating areas by suitability class and generating historical climate series.